Investigation of Education Faculty Students’ Health Perception Levels and Healthy Life Styles in the Covid-19 Process - Bozkurt, Eyup; Erdoğan, Ramazan; Tel, Mikail; Aydemir, İsa and Çelikel, Baha Engin (Progress in Nutrition, 2022)
Objective: With the increase of the Covid-19 epidemic, societies around the world have been exposed to different restrictions. Turkey has also implemented some restrictions in daily-life to reduce the rate of coronavirus spread. This research was conducted to provide a better understanding of changes in health perception and healthy lifestyle habits of university students due to the Covid-19 restrictions. Method: The research group consisted of 1032 (480 Female, 552 Male) volunteer students from the education faculties of Fırat and Mustafa Kemal University. As data collection tool, an online questionnaire form, in which participants’ demographic information, healthy lifestyles and health perception levels were questioned, was used. The data were analyzed using the SPSS package program. Results: The majority of the research group did not do physical activity regularly and consumed two main meals a day and the most skipped meal was lunch with the rate of 55.2%. Students reporetd consuming foods such as cakes/cookies/biscuits most for their snacks, 28.5% of them consumed 1.5 liters of liquid daily. The students’ perception of health scale total score average was 48.15 ± 4.06, the scale sub-dimensions mean score control center mean score was 14.55 ± 1.70, the certainty point average was 15.29 ± 2.85, the average score of importance of health was 9.70±1.62, and the average score of self-awareness was 8.59 ± 1.14. According to the gender variable, male students’ perception of health scale and all sub-dimensions mean scores were higher than female students. It was observed that students who received nutrition education had higher mean scores than students who did not receive nutrition education. It was determined that students without a chronic illness had higher mean scores than students with a chronic illness except for the certainty and self-awareness sub-dimensions. Conclusion: The health perceptions of the students were at a moderate level, and their healthy lifestyle and physical activity levels were negatively affected. In line with these results, it is thought that the implementation of projects supporting a healthy lifestyle, as well as studies to increase the perception of health of individuals, will be beneficial in protecting and improving public health